Arduino Object Follower with Augmented Reality - Prem Jacob, T; Pravin, A; Asha, P (International Journal of Engineering and Technology, 2018)
This research works we use augmented reality SDK to find the walls and ceilingwhich it sends back to your workstation giving you a digitalrepresentation of your environment.This research work utilizes an Arduino robot running an ESP- 8266 Node MCU that conveys with anandroid mobile phone. The android mobile run an application made in the computer game application Unity 3D. The robot will follow an object using Vuforia's client targets so you can make a trackable object at runtime as long as it has sufficient feature points. We have used the Apple's ARkit for identifying the horizontal and vertical planes.Â